¡El pueblo ayuda al pueblo! - Giesecke Sara Lafosse, Mercedes Patricia (Pontificia Universidad Católica del Perú, 2024)
We wonder how it was possible for the Matico Command to achieve such a quick and effective response in a context of confusion and fear of death. We propose to understand the way in which Comando Matico managed to manage the pandemic crisis, as an instance of cultural and political affirmation from which they updated ancestral knowledge, through their collective and organized action, in the care of Shipibo-Konibo patients with COVID-19 and comorbidities. Since May 15, 2020, they established a type of strategic indigenous health response, to achieve the acceptance of both, the population served and the DIRESA-U and the GOREU, especially during the first two years of the COVID-19 pandemic. We collected information through interviews with members of the Comando Matico, from its official Facebook page, and from interviews with third parties. We reach the conclusion that its effectiveness was based on the strengthening of its identity, of the indigenous organization, in the communication and dissemination in its mother tongue of its knowledge and practices in traditional health.

Nos preguntamos ¿cómo fue posible que el Comando Matico lograra una respuesta tan rápida y eficaz en un contexto de confusión y miedo ante la muerte? Planteamos comprender la manera en que Comando Matico logró manejar la crisis de la pandemia, como una instancia de afirmación cultural y política desde la cual actualizaron los saberes ancestrales, mediante su acción colectiva y organizada, en la atención a pacientes shipibo-konibos con COVID-19 y comorbilidades. Desde el 15 de mayo del 2020, establecieron un tipo de respuesta estratégica sanitaria indígena, para lograr tanto la aceptación de la población atendida como de la DIRESA-U y del GOREU, sobre todo durante los primeros dos años de la pandemia por el COVID-19. Se recogió la información por medio de entrevistas a los miembros del Comando Matico, de su página oficial de Facebook y de entrevistas a terceros. Llegamos a la conclusión que su eficacia se fundamentó en el fortalecimiento de su identidad, de la organización indígena, de la comunicación y difusión en su lengua materna de sus saberes y prácticas en salud tradicional.
The People Help the People!
Keywords: Comando Matico Ucayali; Shipibo ancestral medicine; Shipibo public sphere; Indigenous peoples; COVID-19; Comando Matico Ucayali; Medicina ancestral shipibo; Esfera pública shipibo; Pueblos indígenas; COVID-19; https://purl.org/pe-repo/ocde/ford#5.04.03